LiF Doping of C60 Studied with X-ray Photoemission Shake-Up Analysis. (1st January 2017) - Turak, Ayse; Zgierski, Marek Z.; Dharma-Wardana, M. W. C
Abstract : We report our investigation of the chemical doping mechanism induced by LiF interaction with fullerene thin films. High resolution X-ray photoelectron spectroscopy of the C 1s shake-up satellites and F 1s main core level, supported by density functional calculations, suggest the formation of a charge transfer complex between covalent LiF monomers and dimers and C60 . This interaction was observed in both LiF/C60 and C60 /LiF depositions, suggesting that some charge transfer complexation can occur in these systems even without dissociation.